Global spatiotemporal trends and influencing factors of type 2 diabetes mellitus mortality: estimates and predictions from 1990 to 2040 - Zhang, Yue; Deng, Huan; Zu, Jian; Deng, Yujiao; Tan, Jingyue; Yang, Zhanpeng; Jiao, Yang; Cui, Xiaomeng; Zhang, Lei; Ji, Fanpu; Wang, Yuan (Frontiers in Endocrinology, 2025)
BackgroundTo predict global spatiotemporal trends and influencing factors of type 2 diabetes mellitus (T2DM) mortality.Materials and methodsBased on the Global Burden of Disease 2021 database, we utilized the Bayesian Age-Period-Cohort model to predict the age-standardized mortality rate (ASMR) of T2DM in 2022–2040. The common spatial pattern and risk factors were forecasted using the Bayesian spatiotemporal model. Decomposition analysis determined the contribution of influencing factors to T2DM deaths. Frontier analysis estimated the gaps between countries and the potential to reduce ASMR.ResultsThe global deaths of T2DM have been growing, with ASMR showing an increasing and then gradually decreasing trend in 1990–2040 (AAPC1990–2021, 0.31 [0.21–0.42]; AAPC2022–2040, −0.16 [−0.17 to −0.15]), and they are projected to reach 2,756,631 and 18.63 (8.82–28.43) per 100,000 person by 2040, respectively. The ASMR of males is always higher than that of females except Eastern Mediterranean and increases fastest in the 15–49-year group. South-East Asia will have the largest number of deaths (1,035,666 in 2040) and the fastest growth (AAPC2022–2040, 0.22 [0.216–0.228]) in 2022–2040, but Africa will always have the highest ASMR. Age structure contributes more than 58.80% to the increase in deaths except Africa. There are 72 countries with a higher ASMR in 2040 compared to 2021, and 86 countries will have a heavier burden in 2022–2040. High-middle SDI countries have a higher ASMR with huge potential to reduce them.ConclusionsThe global deaths of T2DM have been growing, Africa will always have the highest ASMR. Age structure will be the main factor influencing T2DM mortality across regions.